Urgensi Penerapan Insolvency Test dalam Penyelesaian Kepailitan dan PKPU di Indonesia Berdasarkan Undang-Undang Nomor 37 Tahun 2004 - Nugraha, Lingga; Vic S., Binsar Jon (Pascasarjana UDA, 2023)
The implementation of bankruptcy testing in the bankruptcy legal system in Indonesia is proposed as a step to improve justice and legal certainty for debtors and creditors. The bankruptcy test aims to ensure that the debtor is truly unable to pay his debts before being declared bankrupt. Although the current bankruptcy law does not explicitly regulate the bankruptcy test, its implementation is considered important to prevent bankruptcy abuse by irresponsible creditors. In this article, we discuss a comparison of the existing bankruptcy system with the need to implement the bankruptcy test, as well as the challenges that may arise, both from legal, administrative, and socio-economic aspects. Recommendations for changes to the Bankruptcy Law, strengthening supervision, and law enforcement are also proposed to ensure the implementation of the bankruptcy test is effective. By implementing the right bankruptcy test, it is hoped that the Indonesian bankruptcy system can be more transparent and fair.